Humidity effect on adsorption kinetics of ammonia onto electrospun SnO2 nanofibers - Omur, Birsel Can (IOP Publishing Ltd, 2019)
Tin dioxide nanofibers were successfully synthesized by electrospinning homogeneous solution of SnCl4 center dot 5H(2)O in polyvinyl alcohol (PVA) and the potential of SnO2 nanofibers as ammonia sensing element at room temperature were also investigated. A logarithmic dependence of sensitivity on ammonia concentration was observed. We further investigate the effect of relative humidity between 0% and 70% on ammonia sensing performance of SnO2 nanofibers based conductometric sensor for the first time. Sensing experiments showed that both the baseline sensor current and the responserecovery characteristics of the SnO2 based sensor modified by pre humidification of sensing layer' surface. To study the adsorption kinetics pseudo first order and Elovich models was used and the first order kinetic model best describes the ammonia adsorption onto the SnO2 nanofibers for low concentrations (<= 80 ppm) of ammonia, irrespective of humidity level. On the other hand, the results describe the best representation of Elovich model, as evidenced by the high correlation coefficients, for high concentrations of ammonia gas.
Keywords: ammonia sensing; electrospinning; humidity effect; response time; adsorption kinetics; GAS-SENSING PROPERTIES; TIN OXIDE; SENSOR; SENSITIVITY; CHEMISORPTION; SURFACE; Materials Science